A survey on Reversible Watermarking Techniques for Medical Image - Hazra, Subhasis; Mandal, Himadri; Jana, Poulami (International Journal of Computer Sciences and Engineering, 2025)
Recently Healthcare system becomes very much important in every days life. Medical images play an important role for clinical purposes and also for research of medical science. These images are very sensitive and can be modified easily with existing image processing tools. Faithfull recovery of these images is also very important for proper diagnosis. Some reversible watermarking can fulfill most of these requirements. In this paper we discuss some reversible watermarking schemes which are suitable for the medical imaging applications.